eGirls, eCitizens Putting Technology, Theory and Policy into Dialogue with Girls' and Young Women's Voices - Bailey, Jane (Law, Technology and Media, 2015)
eGirls, eCitizens is a landmark work that explores the many forces that shape girls' and young women's experiences of privacy, identity, and equality in our digitally networked society. Drawing on the multi-disciplinary expertise of a remarkable team of leading Canadian and international scholars, as well as Canada's foremost digital literacy organization, MediaSmarts, this collection presents the complex realities of digitized communications for girls and young women as revealed through the findings of The eGirls Project (www.egirlsproject.ca) and other important research initiatives. Aimed at moving dialogues on scholarship and policy around girls and technology away from established binaries of good vs bad, or risk vs opportunity, these seminal contributions explore the interplay of factors that shape online environments characterized by a gendered gaze and too often punctuated by sexualized violence. Perhaps most importantly, this collection offers first-hand perspectives collected from girls and young women themselves, providing a unique window on what it is to be a girl in today's digitized society.